2016
DOI: 10.3847/0004-6256/151/6/154
|View full text |Cite
|
Sign up to set email alerts
|

Second Epoch Vlba Calibrator Survey Observations: VCS-Ii

Abstract: Six very successful VLBA calibrator survey campaigns were run between 1994 and 2007 to build up a large list of compact radio sources with positions precise enough for use as VLBI phase reference calibrators. We report on the results of a second epoch VLBA Calibrator Survey campaign (VCS-II) in which 2400 VCS sources were re-observed at X and S bands in order to improve the upcoming third realization of the International Celestial Reference Frame (ICRF3) as well as to improve their usefulness as VLBI phase ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 20 publications
2
49
0
Order By: Relevance
“…where the quoted uncertainties represent the 1-σ confidence interval and take into account the statistical uncertainties in the image (0.2 mas in both α and δ), the uncertainty in the phase calibrator position (0.1 mas; Beasley et al 2002;Gordon et al 2016), and the estimated uncertainties associated with the phase referencing technique (0.06 and 0.04 mas for α and δ, respectively; Pradel et al 2006 consistent with the one reported from the FIRST survey (Law et al 2018), as well as the preliminary results published in Marcote et al (2018). The measured flux density on 2018 September 18 follows the declining trend of the light-curve reported from observations with the Karl G. Jansky Very Large Array, VLA (see Fig.…”
Section: On the Persistent Emissionmentioning
confidence: 99%
“…where the quoted uncertainties represent the 1-σ confidence interval and take into account the statistical uncertainties in the image (0.2 mas in both α and δ), the uncertainty in the phase calibrator position (0.1 mas; Beasley et al 2002;Gordon et al 2016), and the estimated uncertainties associated with the phase referencing technique (0.06 and 0.04 mas for α and δ, respectively; Pradel et al 2006 consistent with the one reported from the FIRST survey (Law et al 2018), as well as the preliminary results published in Marcote et al (2018). The measured flux density on 2018 September 18 follows the declining trend of the light-curve reported from observations with the Karl G. Jansky Very Large Array, VLA (see Fig.…”
Section: On the Persistent Emissionmentioning
confidence: 99%
“…The precise location of A-2 is α=19:59:28.32345, δ=+40:44:01.9133 (J2000, ±1 mas), referenced to the previously known astrometric position of the nucleus (established to be α nuc =19:59:28.35648, δ nuc =+40:44:02.0963, Gordon et al 2016) in the ICRF2 frame (Fey et al 2015). The projected offset from the nucleus is 418 mas, or 458 pc.…”
Section: Vlba Observationsmentioning
confidence: 99%
“…The jumps in the number of sources ( Fig. 1f) are caused mainly by special observing programs VLBA Calibrator Survey (VCS) at the VLBA network 7 (Gordon et al (2016) and references therein).…”
Section: General Statistics Of the Observationsmentioning
confidence: 99%